Study of Sociodemographic Profile of victims in Road Traffic Accidents: An Autopsy-Based Study at a Tertiary Care Centre in Haryana (Indian Journal of Forensic Medicine & Toxicology, 2023)
Road traffic accidents are considered one of the important general health concerns, as they result in numerousinjuries and deaths worldwide. India is a developing nation which experiences very high rate of such accidents.This study was planned to study the sociodemographic profile of victims of fatal RTAs involving different typesof vehicles, so as to widen the database for developing the preventive measures that could reduce morbidityand mortality in such cases. A retrospective study was conducted on one hundred cases of road traffic accidentsbrought for medicolegal autopsy to mortuary of Pt. B.D Sharma PGIMS Rohtak over a period of one year. Theirage, gender, region and other socioeconomic factors were studied.
Keywords: Road Traffic Accidents, sociodemographic profile